Development of a high-speed imaging system for real time evaluation and monitoring of cardiac engineered tissues - Belzil, Antoine; Gélinas, Roselle; Comtois, Philippe (Frontiers in Bioengineering and Biotechnology, 2024)
Stem cell derived cardiac monolayers have high potential for tissue regeneration, in vitro drug testing and disease modeling. However, current differentiation protocols are still sub-optimal, resulting in cultures with variable yields and properties. We propose a high-speed lenseless imaging system, integrated with an electrical stimulation unit, to optimize the generation of these cultures. This tool relies on the variations of cellular patterns, during contraction, measured by digital imaging. The imaging system can monitor cardiac cell sheet function and structure, providing the necessary tools to quickly evaluate engineered monolayer. It can record high speed videos and capture high resolution images, from which tissue spatial organization and contractile characteristics can be obtained. Validation of the system was performed using cardiomyocytes derived from human induced pluripotent stem cell and neonatal rat cardiomyocytes. The imaging system allows the observation, acquisition and analysis of important data relating to contractile activity development of cardiac cells, making it a promising tool for optimization in cardiac tissue engineering.